ATTITUDE OF LATVIAN PEOPLE TOWARDS WILDLIFE - Pētersons, Andris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The wildlife values orientation and attitude towards wildlife has become a hot topic nowadays in Latvia because the management of preservation and conservation of wildlife must be based on the understanding of the general public. Furthermore Latvia is considered to be one of the more densely forested countries in Europe with 50% of its territory covered with forest.This article examines the wildlife values orientation of different groups of people from six regions of the country towards wildlife. Catherine M. Hill, Amanda D. Webber, Nancy E. C. Priston studies of conflicts in society about wildlife (2017) show that these conflicts rise because of different values between different human groups. Wildlife value orientation framework used in this study is taken from early studies of Fulton, Manfredo and Lipscomb (1996), which was later developed by Teel, Dayer, Manfredo, Bright (2005).According to the data of a nationwide survey conducted by the author all respondents are divided into “utilitarians”, people who consider that wildlife exists for human use and enjoyment; “mutualists”, people who consider humans and wildlife live side by side as parts of one big family, “pluralists” who share both the “utilitarian” and the “mutualist” point of view and take one or the other side in different situations and “distanced”, people who lack well - formed value orientation, indicating very little interest.Respondents were categorized into four wildlife value orientation types based on their responses to 24 statements. The wildlife value orientations among different groups of people were compared according to their age, gender, education, level of income, place of living and place where their childhood was spent. The attitude of people with different wildlife values and general attitude of all people towards hunters was established.